2009
DOI: 10.1055/s-0029-1220787
|View full text |Cite
|
Sign up to set email alerts
|

The Risk of Congenital Malformations and Other Neonatal and Maternal Health Outcomes among Licensed Cosmetologists

Abstract: This study sought to determine if cosmetologists in New York State (NYS) have a higher risk of complications of labor/delivery or congenital malformations and poor neonatal health indicators among their offspring compared with Realtors and the general population. This retrospective cohort study matched licensing records for cosmetologists and realtors to birth records and the NYS Congenital Malformations Registry from 1997 to 2003. A random sample of NYS birth certificates, frequency matched to cosmetologists … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 16 publications
0
10
0
Order By: Relevance
“…However, in one case–control study from the United States of America (USA) a borderline significance was found for congenital malformations (ventricular septal defect in newborns), 38 based on 2 cases of ventricular septal defect (VSD) in newborns of 26 fathers employed in hairdressing (OR 2.7, 95% CI 1.0–7.5). Similarly, some indices of poor neonatal or maternal health were found to be associated with maternal occupation as a hairdresser in one cohort study from the USA 39 . Specifically, newborns of mothers employed as hairdressers had significantly higher odds in comparison with control group of mothers employed as real‐estate agents for low 1‐min Apgar score (Appearance, Pulse, Grimace, Activity, and Respiration score; OR 1.33, 95% CI 1.09–1.63), low 5‐min Apgar score (OR 2.02, 95% CI 1.04–3.94), pregnancy‐induced hypertension (OR 1.34, 95% CI 1.01–1.76), slowed labor with delayed delivery (OR 1.31, 95% CI 1.12–1.54), precipitous labor (OR 1.52, 95% CI 1.07–2.15), and postpartum hemorrhage (OR 2.12, 95% CI 1.26–3.58).…”
Section: Resultsmentioning
confidence: 88%
See 3 more Smart Citations
“…However, in one case–control study from the United States of America (USA) a borderline significance was found for congenital malformations (ventricular septal defect in newborns), 38 based on 2 cases of ventricular septal defect (VSD) in newborns of 26 fathers employed in hairdressing (OR 2.7, 95% CI 1.0–7.5). Similarly, some indices of poor neonatal or maternal health were found to be associated with maternal occupation as a hairdresser in one cohort study from the USA 39 . Specifically, newborns of mothers employed as hairdressers had significantly higher odds in comparison with control group of mothers employed as real‐estate agents for low 1‐min Apgar score (Appearance, Pulse, Grimace, Activity, and Respiration score; OR 1.33, 95% CI 1.09–1.63), low 5‐min Apgar score (OR 2.02, 95% CI 1.04–3.94), pregnancy‐induced hypertension (OR 1.34, 95% CI 1.01–1.76), slowed labor with delayed delivery (OR 1.31, 95% CI 1.12–1.54), precipitous labor (OR 1.52, 95% CI 1.07–2.15), and postpartum hemorrhage (OR 2.12, 95% CI 1.26–3.58).…”
Section: Resultsmentioning
confidence: 88%
“…To determine if hairdressing occupation is still significantly associated with adverse effects on reproduction, studies which included effects diagnosed from 1995 onward were analyzed (Table 3, N = 6) 38–43 . In summary, none of six studies with various designs (case–control, retrospective cohort, prospective cohort, and cross‐sectional) investigating outcomes including menstrual disorders, congenital malformations, fetal loss, small‐for‐gestational age children, and preterm delivery showed a significantly increased risk in hairdressers.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Some studies have reported increases in the risks of spontaneous abortions [24], SGA [38] and low birth weights of children [39], as well as orofacial clefts [13]. Other studies did not find any association between occupational exposure among cosmetologists and menstrual disorders [40], infertility [41], congenital malformations [42], and other adverse pregnancy outcomes [43]. …”
Section: Discussionmentioning
confidence: 99%